Operating room nurse's awareness and implementation status of the prevention of patient's intraoperative acquired pressure injuries: design and validation of a questionnaire - Zou, Zhenya; Lv, Shijiao; Gao, Qian; Zhou, Xiaoyang; Mao, Jinbao (Frontiers in Surgery, 2024)
Aim: To compile the awareness and implementation status of patients with intraoperative acquired pressure injuries prevention by operating room nurses and to test its reliability and validity.Design: This is an equipment development research based on recommendations for developing a reliable and valid questionnaire.The research was carried out in two phases from February to November 2022. Through a panel discussion, expert consultation, and literature review, the questionnaire for operating room nurses on the current status of awareness and implementation of the prevention of intraoperative acquired pressure injuries was preliminarily formulated. The formal questionnaire was developed through validity analysis, reliability analysis and item analysis, and reliability and validity tests were conducted. Moreover, according to the questionnaire survey results, confirmatory factor analysis was carried out to construct the structural equation model.The initial questionnaire consisted of five dimensions with 48 items, which was finalized to five dimensions with 38 items after reliability and validity testing and analysis. The five dimensions included implementation of intraoperative acquired pressure injuries prevention, intraoperative acquired pressure injuries preventing cognitive conditions, preoperative intraoperative acquired pressure injuries preventing cognitive conditions, basic knowledge of pressure injuries, and implementation of intraoperative acquired pressure injuries prevention in special patients. Cronbach's α of the overall questionnaire was 0.969 while that of each dimension was 0.846-0.959.The KMO value of structural validity was 0.945 (P < 0.001), and the contribution rate of cumulative variance was 70.694%. The fitting of confirmatory factor analysis was found to be generally ideal:  2 /df=2.382, RMR=0.027, TLI=0.894, RMSEA=0.072, 2 IFI=0.905, CFI=0.904.The study and design of the questionnaire for operating room nurses on the current status of awareness and implementation of the prevention of intraoperative acquired pressure injuries are scientific and rational, providing a scientific basis for the standardized reform of hospitals and the optimization of the intraoperative acquired pressure injuries management system of the operating room.